2002
DOI: 10.1039/b202347b
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural studies of the copper promoted iron oxide/chromia water-gas shift catalyst

Abstract: The microstructure of an iron oxide based high temperature water-gas shift (WGS) catalyst has been studied by X-ray diffraction (XRD), high resolution electron microscopy (HREM), high spatial resolution energy dispersive X-ray analysis (STEM-EDX) and X-ray photoelectron spectroscopy (XPS). The iron oxide contains a chromia additive that structurally stabilises the catalyst. Chemical microanalysis indicates that the chromia forms a solid solution within the magnetite Fe 3 O 4 lattice and that no discrete chromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 22 publications
4
69
0
Order By: Relevance
“…However, the evolution of modern techniques has shed a new light on this matter. Using a combination of XPS, XRD and highresolution electron microscopy (Edwards et al, 2002) it was recently shown that Cr forms a solid solution in magnetite. In a freshly reduced Fe/Cr catalyst containing 8% Cr, only a single spinel phase was detected by XRD and by high-resolution electron microscopy (HREM).…”
Section: Reactormentioning
confidence: 99%
See 2 more Smart Citations
“…However, the evolution of modern techniques has shed a new light on this matter. Using a combination of XPS, XRD and highresolution electron microscopy (Edwards et al, 2002) it was recently shown that Cr forms a solid solution in magnetite. In a freshly reduced Fe/Cr catalyst containing 8% Cr, only a single spinel phase was detected by XRD and by high-resolution electron microscopy (HREM).…”
Section: Reactormentioning
confidence: 99%
“…In the paper of Edwards et al (2002) it is described how an Fe/ Cr/Cu catalyst sample was aged for 1000 h at 370 C with a foreseeable loss of surface area from 50 to 17 m 2 /g. Nonetheless the sample occasionally displayed 7e12 nm particles of CuO (the sample must have become oxidised) in contact with magnetite particles as evidenced by HREM.…”
Section: Reactormentioning
confidence: 99%
See 1 more Smart Citation
“…The WGS reactor currently represents the largest volume of any catalyst in role of the Cr 2 O 3 addition on the stabilization of the catalyst structure is still unclear. Edwards et al [15] proposed a model for the high stabilizing effect of chromium whereby a shell of chromium-enriched material is formed on each catalyst grain, but the mechanism by which promotion occurs is still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Industria WGS catalysts are typically 92 wt % Fe3O4/8 wt % Cr2O3 that serve as activ reaction temperatures close to 400 °C [2]. Numerous research studies h enhancing the stability and activity of these catalysts through the addition o Ce, Hg, Ag and Rh) that can stabilize the iron-chromium structure and provi for the chemical reaction [3][4][5][6][7][8][9][10][11][12][13]. A previous study has shown that the Fe/Cr/Cu high-temperature (HT) water-gas shift (WGS) catalysts chan programmed reduction profiles, generally causing more consumption of Previous studies also showed that lanthana increases the thermal stabil perovskite-like unsupported chromium-free iron-based catalysts for the wat Co-based catalysts for the Fischer-Tropsch synthesis reaction [11][12][13].…”
Section: Introductionmentioning
confidence: 99%